Strategic Decision-Making for Low-Sulfur Gasoline Production at RU III Plaju Using an Integrated AHP–TOPSIS Framework for the Pre-Feasibility Gate in Support of Indonesia's Net Zero Emissions 2060 - Irza Afrianto; Utomo Sarjono Putro (Eduvest - Journal of Universal Studies, 2026)
Indonesia’s energy transition toward Net Zero Emissions (NZE) 2060 requires the refining sector to improve fuel quality while maintaining energy security and economic sustainability. One of the critical challenges faced by PT Kilang Pertamina Internasional Refinery Unit III (RU III) Plaju is the inability to consistently produce low-sulfur gasoline that meets Euro IV/V standards due to limited desulfurization capability. This condition creates a strategic decision challenge involving technical, economic, regulatory, and sustainability considerations. This study aims to determine the most feasible strategic alternative for low-sulfur gasoline production at RU III Plaju by developing an integrated decision-making framework for the pre-feasibility stage. The research applies a sequential mixed-methods approach combining SWOT analysis, IFE–EFE matrix evaluation, TOWS analysis, and Multi-Criteria Decision-Making (MCDM) using the AHP–TOPSIS framework. Expert judgments from refinery managers, engineers, and technical specialists were used to evaluate strategic alternatives based on strategic viability, economic viability, technical compliance, and regulatory sustainability criteria. The results indicate that the construction of a Hydrodesulfurization/Gasoline Sulfur Handling (HDS/GSH) unit is the optimal alternative, achieving the highest TOPSIS closeness coefficient of 0.8481. Sensitivity analysis confirms the robustness of this ranking under variations in criteria weights. The study concludes that the proposed AHP–TOPSIS framework provides a transparent, systematic, and reliable approach for strategic investment decisions, supporting RU III Plaju’s long-term competitiveness and Indonesia’s NZE 2060 objectives.